Analisis Celebrity Endorser dan Core Product terhadap Keputusan Pembelian Produk KF Skin Care (Studi Kasus Pada Mahasiswa Universitas Islam Lamongan) - Evi Yulia (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
This study aims to determine which celebrity endorsers and core products have a partial and simultaneous effect on purchasing decisions for KF skincare products. In addition, to find out the most dominant variables among celebrity endorsers and core products on purchasing decisions for KF skincare products in students of the Islamic University of Lamongan. The data collection method used in this research is descriptive test, validity test, reliability test, classical assumption test, multiple linear regression test, t test and F test. KF Skincare for students of the Faculty of Economics, Islamic University of Lamongan. t test results show tcount> ttable. While the second study shows that celebrity endorsers and core products have a simultaneous effect on purchasing decisions for KF Skincare products for students of the Faculty of Economics, University of Islam Lamongan. The results of the F test show that Fcount> Ftable and the most dominant variable influencing the decision to buy KF Skincare products for students of the Faculty of Economics, University of Islam Lamongan is the core product variable.